Evaluation of vestibulo-ocular reflex with functional head impulse test in healthy individuals: normative values - Cengiz, Deniz Uğur; Erbek, Hatice Seyra; Çolak, Sanem Can; Kurtcu, Büşra; Demirel Birişik, Sümeyye; Karababa, Ercan; Kuşman, Buşra; Özdemir, Emre Akgün; Işık, Mehmet; Demir, İsmail (Frontiers in Neurology, 2023)
Objectives This study aimed to determine the normative values of the functional head impulse test (fHIT) test in healthy young adults. Materials and methods The study included 100 individuals, 58 females and 42 males, aged 20–25 years. Beon Solution Zero Branco (TV) fHIT test was applied to all participants. FHIT results were analyzed in terms of lateral-posterior–anterior semicircular canals (SSCs), gender, and right–left ear. Results In the fHIT test, for the lateral SSC the mean percent correct answer (%CA) values for 4,000–6,000°/s2 and 1,000–7,000°/s2 were 88.52 ± 9.04 and 89.91 ± 6.95, respectively; for the posterior SSC, the mean %CA values for SSC 3000–6,000°/s2 and 1,000–7,000°/s2 were 90.63 ± 8.69 and 91.16 ± 7.42, respectively; for the anterior SSC, the mean %CA values for 3,000–6,000°/s2 and 1,000–7,000°/s2 were 91.21 ± 7.96 and 91.49 ± 7.13, respectively. There was no statistically significant difference between the right and left ear in %CA values at all accelerations in all SSCs (p > 0.05). There was a statistically significant difference between genders in the mean %CA values for 6,000–7,000°/s2, 4,000–6,000°/s2, and 1,000–7,000°/s2 in the lateral SSC and 3,000–6,000°/s2 in the anterior SSC (p < 0.05). Conclusion The FHIT is a noninvasive test battery that functionally evaluates the VOR of the six semicircular canals. In clinical use, the determination of normative values at all accelerations (1,000–7,000 degrees/s2) constitutes an important database for future studies to distinguish pathologic results.